Exploring the Role of Social Media in Health Promotion - Stellefson, Michael; Chaney, J. Don; Chaney, Beth H.; Paige, Samantha R. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The use of social media in public health education/promotion has been increasing due, in part, to its ability to remove physical access and geographical barriers for users. Specifically, social media provides an outlet to increase and promote translational health communication strategies and the effective dissemination of health information and data in ways that allow users to not only utilize, but also to create and share pertinent health information. Although social media applications in public health and health promotion have yielded success in terms of generating support structures and networks for effective health behavior change, there are challenges and complications associated with use of social media that also need to be addressed (e.g., managing misinformation, ensuring compliance with privacy protection regulations). This Special Issue aims to explore social media as a translational health promotion tool by bridging principles of health education and health communication. Broadly, this Special Issue is seeking original submissions that examine: (1) the method with which social media users access, negotiate, and create health information that is both actionable and impactful for diverse audiences; (2) strategies for overcoming challenges to using social media in health promotion; and (3) best practices for designing, implementing, and/or evaluating social media campaigns and forums in public health. Special interest will be given to innovative submissions that expand and build upon traditional health education approaches with health communication theories and models. Other manuscript types of interest include relevant position papers, brief reports, and commentaries.